(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
This article investigates clowning performed by women in Brazil from decolonial feminist perspectives, considering comedy as a set of situated geocultural and social practices that are inevitably situated in a context and traversed by relations of gender, race, class, and coloniality. The research examines the practices of Brazilian female clowns since the 1980s, based on a critical bibliographic review, analysis of academic and artistic productions, and previous mappings, understanding them as critical reactivations and performative inscriptions of clowning matrices.